A GIS approach to sediment displacement in mixed sand and gravel beach environments. (1st November 2019) - Hemmingsen, Maree A.; Eikaas, Hans S.; Marsden, David C.J.
Abstract: Mixed sand and gravel beaches pose special management issues as they are morphologically distinct from either pure sand or shingle beaches. On the mixed sand and gravel beaches of the Canterbury Bight, New Zealand, displacement of sediments operates within a two-part sediment transport system. The large sediments are retained in the beaches, while the fine sand, silt, and mud are transported offshore to the continental shelf. While the susceptibility of sediments to size-reduction is dependent on the textural mixture of sediments, the actual size-reduction takes place during sediment transport, or displacement, in the active surf zone of the beach. The authors outline a method that incorporates the sediment reduction susceptibility of beach sediments from the textural mixture, twenty years of wave-hindcast data, and sediment tracer experiments to model sediment displacement in mixed sand and gravel beach environments of the Canterbury Bight. Results show that the textural mix of the sediments influences not only the rate of loss to size-reduction but also the time taken for sediment to be transported along a beach continuum within the surf zone. The authors modelled time-frames to achieve three target percentages of sediment displacement: (1) ten percent, (2) fifty percent, and (3) a range of zero to one hundred percent. Ten percent displacement of sediments was predicted to take between four and eighty-eight weeks, fifty percent displacement between one and sixteen years, and a hundred percent displacement up to two-hundred and thirty years, depending on the textural composition of sediments along the coast based on the actual wave action occurring along this coastline.